"Black Betty" - The new cycle ergometer linking physiology and biomechanics - Brooks, H.; Osborne, M.; Andrews, M.; Jenkins, D. (National Elite Sports Council 2009 Athlete Services Forum - High Performance Programming for Success - 11-12th November - Satellite Program - Applied Physiology Conference 2009 - Australian Institute of Sport, Canberra - 10th, 11th and 13th November, 2009)
The Axis cycle ergometer aka "Black Betty" was purchased by the QAS in 2008. At that stage we were relying on using an SRM cycle ergometer and the Hayes air-braked cycle ergometer for all laboratory testing across BMX, road and track cyclists, however this equipment was limited to providing external power output only. No detail regarding how an athlete actually applies force to the pedals whilst cycling was available to the scientist or athlete and coaches were often asking about the effect of bike setup, training evaluation and possible musculo-skeletal imbalances where they were limited to non-specific evaluation using equipment such as the Cybex or basic gym tests. In recent years, the only method of capturing the pedal force data was to build custom made pedals which contained a number of strain gauges. However because of the technology of the time, these were often tethered so a significant amount of cabling was attached to each pedal, and the rapid rate of pedal development by various manufacturers left many of the custom made pedals obsolete as riders updated their preferences and setups. This new cycle ergometer has instrumented cranks which measure in two dimensions, meaning measurements are independent of the pedal type. Methods Forces are measured at 100 Hz along the axis of the crank (compressive or radial force) and perpendicular to the crank arm (tangential or rotational force). As this is measured in both crank arms, we are able to identify any pedalling asymmetries. We are also able to develop torque profiles and calculate resultant forces throughout the pedal stroke. Discussion/Conclusion This will provide useful information for coaches and as we gain a better understanding of various rider/discipline profiles, will assist coaches in actually "coaching" a cyclist rather than just "training" a cyclist. We have currently integrated the data output from the AXIS cycle ergometer with EMG and video which is all collected and displayed in real time. Our next stage of development will be to incorporate real time kinematic analysis (such as the RETÜL system) which will enable a combined assessment of joint angles and joint powers. Combined with physiological assessment capabilities, this multidisciplinary set up will be a totally integrated system enabling the only (laboratory based) evaluation of changes in various cycling parameters such as position or the effect of particular training stimulus on both physiological responses and the subsequent biomechanical implications.